Activation of TLR2 heterodimers-mediated NF-κB, MAPK, AKT signaling pathways is responsible for Vibrio alginolyticus triggered inflammatory response in vitro. (January 2022) - Wang, Jinxin; Li, Xiaomin; Bello, Babatunde Kazeem; Yu, Guili; Yang, Qiankun; Yang, Haitao; Zhang, Wei; Wang, Lei; Dong, Jingquan; Liu, Gang; Zhao, Panpan
Abstract: Vibrio alginolyticus is an important zoonotic marine pathogenic bacterium. Previous studies on the mechanism of innate immune against V. alginolyticus infection have been limited to aquatic animals, however, how V. alginolyticus activates mammalian immune cells has not been fully clarified. Here, ELISA combined RT-qPCR assays were used to detect the secretion and transcription level of pro-inflammatory cytokines and TLRs during V. alginolyticus infection of mice peritoneal macrophages (PMϕs). Western blotting was used to explore the phosphorylation levels of p38, JNK, ERK, AKT and NF-κB protein. Immunofluorescence assay was used to determine the location of NF-κB protein. Inhibition assay was used to study the role of up-regulated TLR in activated signaling pathways and the role of these pathways in the release of pro-inflammatory cytokines. Our data showed that V. alginolyticus can up-regulate the expression levels of IL-1β, IL-6, IL-12 and TNF-α in PMϕs. In addition, V. alginolyticus stimulation activated the phosphorylation of p38, JNK and ERK were TLR2 heterodimers-dependent, whereas inhibitors of SB203580 (p38), SCH772984 (ERK) and SP600125 (JNK) significantly reduced IL-1β, IL-6, IL-12 and TNF-α production. We further revealed that V. alginolyticus activated the signaling pathways of AKT via TLR2 heterodimers. The inhibitor of MK-2206 2HCl (AKT) negatively regulated the IL-1β, IL-6 and TNF-α release levels. Moreover, V. alginolyticus infection of PMϕs resulted in TLR2 heterodimers-mediated activation of NF-κB and induced translocation of phosphorylated NF-κB protein from the cytoplasm into the nucleus via IκBα degradation. V. alginolyticus induced IL-1β, IL-6, IL-12 and TNF-α release were blocked by the specific NF-κB inhibitor, BAY 11–7082. Taken together, our results suggested that activation of the TLR2 heterodimers-mediated downstream signaling pathways NF-κB, MAPK and AKT is responsible for inflammatory response during Vibrio alginolyticus infection in vitro . Highlights: V. alginolyticus activate TLR2-mediated MAPK, AKT and NF-κB pathways in mouse PMϕs. V. alginolyticus activate MAPK and NF-κB pathways to enhance inflammatory response. Cytokines levels are negatively regulated by AKT pathway in infected PMϕs.